Nonlinear optical properties of pyrimidine chromophores. (November 2020) - Fecková, Michaela; le Poul, Pascal; Bureš, Filip; Robin-le Guen, Françoise; Achelle, Sylvain
Abstract: The large library of nonlinear optical (NLO) chromophores based on pyrimidine scaffold is discussed in this review. Since the first examples described thirteen years ago, the interest in pyrimidine push-pull NLO chromophores has increased dramatically, especially for second harmonic generation and two photon absorption. More than 130 properly selected chromophores are presented to demonstrate fundamental structure-property relationships and to highlight key applications of pyrimidine-derived materials. Highlights: The large library of pyrimidine NLO chromophores has been reviewed. Fundamental structure-property relationships were elucidated. Methylpyrimidinium push-pull chromophores are superior second-order NLOphores. 4, 6-Distyrylpyrimidine derivatives proved to be well-established organic chromophores for two-photon absorption.